Quantifying the RR of harm to self and others from substance misuse: results from a survey of clinical experts across Scotland. Issue 4 (24th July 2012) - Taylor, Mark; Mackay, Kirsty; Murphy, Jen; McIntosh, Andrew; McIntosh, Claire; Anderson, Seonaid; Welch, Killian
Abstract : Objective: To produce an expert consensus hierarchy of harm to self and others from legal and illegal substance use. Design: Structured questionnaire with nine scored categories of harm for 19 different commonly used substances. Setting/participants: 292 clinical experts from across Scotland. Results: There was no stepped categorical distinction in harm between the different legal and illegal substances. Heroin was viewed as the most harmful, and cannabis the least harmful of the substances studied. Alcohol was ranked as the fourth most harmful substance, with alcohol, nicotine and volatile solvents being viewed as more harmful than some class A drugs. Conclusions: The harm rankings of 19 commonly used substances did not match the A, B, C classification under the Misuse of Drugs Act. The legality of a substance of misuse is not correlated with its perceived harm. These results could inform any legal review of drug misuse and help shape public health policy and practice.